Research progress of pain catastrophizing in patients with lumbar disc herniation - Xiong Ting; Piao Long-Fan (Sciendo, 2024)
Pain catastrophization is one of the negative emotional factors and an important psychological factor associated with patients with lumbar disc herniation (LDH). Currently, the concept of pain catastrophization of LDH is relatively mature abroad; however, there are only few research studies on this in China. To understand the status quo of pain catastrophization (PC) in patients with LDH and its influencing factors, the intervention measures of PC and their efficacy were further analyzed. In the present paper, the research status of PC at home and abroad is briefly expounded, and the influencing factors and clinical intervention measures for PC are analyzed. This paper reviews the concept of PC, the assessment tools, influencing factors, and the relevant intervention measures. In order to evaluate the pain degree of patients, understand the incidence of pain in patients, and improve the cure rate and quality of life of patients, the basic situation of patients with pain disaster is summarized to provide reference for medical personnel.